Culture’s building blocks: investigating cultural evolution in a LEGO construction task - McGraw, John J.; Wallot, Sebastian; Mitkidis, Panagiotis; Roepstorff, Andreas (Frontiers in Psychology, 2014)
One of the most essential but theoretically vexing issues regarding the notion of culture is that of cultural evolution and transmission: how a group’s accumulated solutions to invariant challenges develop and persevere over time. But at the moment, the notion of applying evolutionary theory to culture remains little more than a suggestive trope. Whereas the modern synthesis of evolutionary theory has provided an encompassing scientific framework for the selection and transmission of biological adaptations, a convincing theory of cultural evolution has yet to emerge. One of the greatest challenges for theorists is identifying the appropriate time scales and units of analysis in order to reduce the intractably large and complex phenomenon of “culture” into its component “building blocks.” In this paper, we present a model for scientifically investigating cultural processes by analyzing the ways people develop conventions in a series of LEGO construction tasks. The data revealed a surprising pattern in the selection of building bricks as well as features of car design across consecutive building sessions. Our findings support a novel methodology for studying the development and transmission of culture through the microcosm of interactive LEGO design and assembly.